Online Detection of Vacuum Level of Circuit Breaker Based on Terahertz Wave Return Loss - LUO Hong-hong; ZHANG Xue-min; CHENG Yi-bin; ZHANG Hui-yuan (Journal of Harbin University of Science and Technology, 2022)
For the online detection of vacuum degree in circuit breaker interrupter chamber, based on the principle of terahertz detection technology, the method of online detection of vacuum degree in circuit breaker using terahertz wave return loss is adopted, and the theoretical basis of continuous wave terahertz return loss applied to online vacuum degree monitoring is analyzed.FDTD is used to simulate the return loss of circuit breaker interrupter at different pressures, and four vacuum bubbles with different vacuum degrees are used for terahertz detection experiments.The comparison between the experimental data and the simulation data shows that as the vacuum level decreases, the return loss of the terahertz spectrum gradually increases, i.e., the return loss spectrum obtained by using continuous wave terahertz imaging technology can distinguish the change of vacuum level, which proves the feasibility of the vacuum level online detection method proposed in this paper.